Ganoderma spore lipid ameliorates docetaxel, cisplatin, and 5-fluorouracil chemotherapy-induced damage to bone marrow mesenchymal stem cells and hematopoiesis - Haohui Lin; Manhon Chung; Jingchun Sun; Yi Yang; Li Zhang; Xiaohua Pan; Minghui Wei; Sa Cai; Yu Pan (BMC Complementary Medicine and Therapies, 2024)
Abstract Background A triplet chemotherapy regimen of docetaxel, cisplatin, and 5-fluorouracil (TPF) is used to treat head and neck squamous cell carcinoma; however, it is toxic to bone marrow mesenchymal stem cells (BMSCs). We previously demonstrated that Ganoderma spore lipid (GSL) protect BMSCs against cyclophosphamide toxicity. In this study, we investigated the protective effects of GSL against TPF-induced BMSCs and hematopoietic damage. Methods BMSCs and C57BL/6 mice were divided into control, TPF, co-treatment (simultaneously treated with GSL and TPF for 2 days), and pre-treatment (treated with GSL for 7 days before 2 days of TPF treatment) groups. In vitro, morphology, phenotype, proliferation, senescence, apoptosis, reactive oxygen species (ROS), and differentiation of BMSCs were evaluated. In vivo, peripheral platelets (PLTs) and white blood cells (WBCs) from mouse venous blood were quantified. Bone marrow cells were isolated for hematopoietic colony-forming examination. Results In vitro, GSL significantly alleviated TPF-induced damage to BMSCs compared with the TPF group, recovering their morphology, phenotype, proliferation, and differentiation capacity (p < 0.05). Annexin V/PI and senescence-associated β-galactosidase staining showed that GSL inhibited apoptosis and delayed senescence in TPF-treated BMSCs (p < 0.05). GSL downregulated the expression of caspase-3 and reduced ROS formation (p < 0.05). In vivo, GSL restored the number of peripheral PLTs and WBCs and protected the colony-forming capacity of bone marrow cells (p < 0.05). Conclusions GSL efficiently protected BMSCs from damage caused by TPF and recovered hematopoiesis.